1992
DOI: 10.1159/000261494
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization and Inhibition by Fluoride of Enolase from Streptococcus mutans DSM320523

Abstract: Enolase from Streptococcus mutans has been purified to homogeneity by a three-step procedure. As shown by analytical ultracentrifugation and poly-acrylamide gel electrophoresis under denaturing conditions, the purified enzyme is an octamer with molecular weight Mr = 360 kDa, composed of eight identical subunits with Mr = 45 kDa. The kinetic parameters of S. mutans enolase in the presence of 1 mM Mg2+ are Aspec = 130IU × mg-1 and KM = 0.44 mM as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 14 publications
3
37
0
Order By: Relevance
“…Fluoride is also known to inhibit bacterial acid production in vitro (Hamilton, 1990;Marquis, 1990;Jenkins, 1999) and plaque acid production in vivo (Tatevossian, 1990;Vogel et al, 2002). Competitive inhibition by fluoride of enolase, an enzyme in the Embden-Meyerhof-Parnas pathway (the EMP pathway) extracted from Streptococcus mutans and other plaque bacteria (Kaufmann and Bartholmes, 1992;Guha-Chowdhury et al, 1997), suggested that enolase is the target enzyme by fluoride inhibition. The addition of fluoride to a cell suspension of S. mutans, S. sobrinus, and S. sanguinis results in the intracellular accumulation of 3-phosphoglycerate and 2-phosphoglycerate (enolase substrate) and the decrease of phosphoenolpyruvate (enolase product) in the EMP pathway (Hata et al, 1990;Maehara et al, 2005), confirming the inhibition of enolase by fluoride; however, the inhibitory mechanism of fluoride has not been confirmed in plaque biofilm, consisting of multispecies of bacteria, where they may behave differently compared with in vitro behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride is also known to inhibit bacterial acid production in vitro (Hamilton, 1990;Marquis, 1990;Jenkins, 1999) and plaque acid production in vivo (Tatevossian, 1990;Vogel et al, 2002). Competitive inhibition by fluoride of enolase, an enzyme in the Embden-Meyerhof-Parnas pathway (the EMP pathway) extracted from Streptococcus mutans and other plaque bacteria (Kaufmann and Bartholmes, 1992;Guha-Chowdhury et al, 1997), suggested that enolase is the target enzyme by fluoride inhibition. The addition of fluoride to a cell suspension of S. mutans, S. sobrinus, and S. sanguinis results in the intracellular accumulation of 3-phosphoglycerate and 2-phosphoglycerate (enolase substrate) and the decrease of phosphoenolpyruvate (enolase product) in the EMP pathway (Hata et al, 1990;Maehara et al, 2005), confirming the inhibition of enolase by fluoride; however, the inhibitory mechanism of fluoride has not been confirmed in plaque biofilm, consisting of multispecies of bacteria, where they may behave differently compared with in vitro behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This may be the result of fluoride release from the coating material. Fluoride can reduce acid production by S. mutans through a number of mechanisms 50) , including inhibition of the glycolytic enzyme enolase 51,52) and the proton-extruding ATPase 53,54) . The reduced drop of pH on the surface of PRG Barrier Coat could also be related to interference with other intracellular or plaque-associated enzymes in S. mutans, such as acid phosphatase, pyrophosphatase, peroxidase and catalase by released fluoride 55) .…”
mentioning
confidence: 99%
“…The effects of fluoride on cariogenic Streptococcus mutans and other bacteria have been extensively studied. Fluoride inhibits enolase, a glycolytic enzyme (5,6), inhibits F-ATPase activity resulting in less acidurance (7,8), reduces glucan-binding lectin activity (9), and decreases glucose incorporation (10). However, the effects of fluoride on group A Streptococci have not been examined.…”
mentioning
confidence: 99%